The role of the combination of Moringa oleifera leaf extract and demineralized freeze-dried bovine bone xenograft (xenograft) as tooth extraction socket preservation materials on osteocalcin and transforming growth factor-beta 1 expressions in alveolar bone of Cavia cobaya - Utari Kresnoadi; Primanda Nur Rahmania; Hera Utami Caesar; Eha Djulaeha; Bambang Agustono; Muhammad Dimas Aditya Ari (Wolters Kluwer Medknow Publications, 2019)
Aim: Alveolar bone resorption, often occurring after tooth extraction, can be minimized through socket preservation. This process uses a combination of Moringa leaf extract and demineralized freeze-dried bovine bone xenograft (DFDBBX) that is expected to generate both transforming growth factor-beta 1 (TGF-β1) expressions as a transcription factor associated with osteoblast differentiation and osteocalcin accelerating alveolar bone formation. This research aimed to analyze the role of the combination of Moringa leaf extract and DFDBBX induced in socket preservation when generating TGF-β1 and osteocalcin expressions. Materials and Methods: The left mandibular incisors of 56 Cavia cobaya were extracted and divided into four groups subjected to different socket preservation treatments. The first group treated with polyethylene glycol, the second group with DFDBBX, the third group with Moringa leaf extract, and the fourth group with a combination of DFDBBX and Moringa leaf extract. The C. cobaya were examined on days 7 and 30, after which the specimens were sacrificed and examined using an immunohistochemical technique. The resulting data were then analyzed using one-way ANOVA and Tukey's honestly significant difference tests. Results: There was a significant difference in TGF-β1 and osteocalcin expressions between the groups (P < 0.05). The highest mean amount of TGF-β1 and osteocalcin was found in the fourth group on both days 7 and 30. Conclusions: The combination of Moringa leaf extract and DFDBBX can effectively generate TGF-β1 and osteocalcin expressions during the preservation of tooth extraction sockets.